Complete nucleotide sequence of wild-type hepatitis A virus: comparison with different strains of hepatitis A virus and other picornaviruses. - Cohen, J I (1987)
The complete nucleotide sequence of wild-type hepatitis A virus (HAV) HM-175 was determined. The sequence was compared with that of a cell culture-adapted HAV strain (R. Najarian, D. Caput, W. Gee, S.J. Potter, A. Renard, J. Merryweather, G.V. Nest, and D. Dina, Proc. Natl. Acad. Sci. USA 82:2627-2631, 1985). Both strains have a genome length of 7,478 nucleotides followed by a poly(A) tail, and both encode a polyprotein of 2,227 amino acids. Sequence comparison showed 624 nucleotide differences (91.7% identity) but only 34 amino acid differences (98.5% identity). All of the dipeptide cleavage sites mapped in this study were conserved between the two strains. The sequences of these two HAV strains were compared with the partial sequences of three other HAV strains. Most amino acid differences were located in the capsid region, especially in VP1. Whereas changes in amino acids were localized to certain portions of the genome, nucleotide differences occurred randomly throughout the genome. The most extensive nucleotide homology between the strains was in the 5' noncoding region (96% identity for cell culture-adapted strains versus wild type; greater than 99% identity among cell culture-adapted strains). HAV proteins are less homologous with those of any other picornavirus than the latter proteins are when compared with each other. When the sequences of wild-type and cell culture-adapted HAV strains are compared, the nucleotide differences in the 5' noncoding region and the amino acid differences in the capsid region suggest areas that may contain markers for cell culture adaptation and for attenuation.